180-Day functional decline among older patients attending an emergency department after a fall. (November 2019) - Miró, Òscar; Brizzi, Berenice N.; Aguiló, Sira; Alemany, Xavier; Jacob, Javier; Llorens, Pere; Herrero Puente, Pablo; Torres Machado, Victoria; Cenjor, Raquel; Gil, Adriana; Rico, Verònica; Álvarez Carretero, María; et al.
Highlights: Functional outcomes of older adults after a fall-related ED visit are less well understood. Three out of 4 older patients attended for a fall in EDs had some degree of functional impairment before the event. One out of 3 cases had a clinically significant functional decline at 180 days. Age ≥85 years, fall-related fracture, hospitalization and post-fall syndrome were associated with 180-day poor outcome. Abstract: Objectives: To determine functional changes and factors affecting 180-day functional prognosis among older patients attending a hospital emergency department (ED) after a fall. Study design: Retrospective analysis from a prospective cohort study (FALL-ER Registry) spanning one year that included individuals aged ≥65 years attending four Spanish EDs after a fall. We collected 9 baseline and 6 fall-related factors. Main outcome measures: Barthel Index (BI) was measured at baseline, discharge and 30, 90 and 180 days after the index fall. Absolute and relative BI changes were calculated. Absolute difference of ≥10 points between BI at baseline and at 180 days was considered a clinically significant functional decline. Results: 452 patients (mean age 80 ± 8 years; 70.8% women) were included. Baseline BI was 79.3 ± 23.1 points. Compared with baseline, functional status was significantly lower at the 4 follow-up time points (-8.7% at discharge; and −6.9%, −7.9% and −9.5% at 30, 90 and 180 days; p < 0.001 for all comparisons in relation to baseline; p = 0.001 for change over time). One hundred and thirty-three (29.6%) patients had a clinically significant functional decline at 180 days. Age ≥85 years (OR = 2.24, 95%CI 1.23–4.08; p = 0.008), fall-related fracture (OR = 2.45, 95%CI 1.43–4.28; p = 0.001), hospitalization (OR = 1.91; 95%CI 1.11–3.29; p = 0.019) and post-fall syndrome (OR = 1.77, 95%CI 1.13-2.77; p = 0.013) were independently associated with 180-day clinically significant functional decline. Conclusion: Patients ≥65 years attending EDs after a fall experience a consistent and persistent negative impact on their functional status. Several factors may help identify patients at increased risk of functional impairment.